L. B. Krause y W. S. Salant (comps.), Worldwide Inflation, Theory and Recent Experience. Washington, D. C., The Brookings Institute, 1977 - Murra, Ricardo (Estudios Demográficos y Urbanos, 1978)
L. B. Krause y W. S. Salant (Comps.), Worldwide Inflation. Theory and Recent Experience, Washington, D. C, The Brookings Institute, 1977.